Flurzusammenlegung und Ausbausiedlung in der Nordostschweiz - Sick, Wolf-Dieter (ERDKUNDE, 1955)
The paper deals with consolidation of field parcels and re-location of farmsteads on the newly consolidated farm land. The author relates this process to the geographical conditions and uses it as an example of the modern tendency towards rationalisation in agriculture. After a general review of the types of settlements and field patterns found, and also of their development, an account is given of the spread of the process of consolidation of holdings in Switzerland and of the way in which this consolidation has been carried out. It has already been accomplished in continuous areas with parishes of considerable extent; besides arable land and meadow land, vineyards, orchards and privately owned forest plots have also been included. Large scale draining projects in damp areas were simultaneously put into effect and numerous new farmsteads have been erected on the now consolidated land. Seen against the background of the regional conditions, four distinct areas can be distinguished. In the northwestern part of the investigated area early settlement in villages with greatly fragmentated open fields, arable farming land and intensive cultivation prevail. In this region the consolidation process has made particularly pronounced progress. In the transitional zone of more varied relief, hamlets and dispersed farmsteads dating from the great clearing period predominate; their land is less fragmentated and mixed farming is typical. Consolidation of holdings has so far made less progress here than in the northwestern region. The mountainous south-eastern part which was settled during the late clearing period is distinguished by dispersed farms and small hamlets. The customs of undivided inheritance and compact holdings are traditional and made a consolidation of holdings unnecessary. In contrast to this region, the old settled Rhine valley shows again a high degree of land fragmentation and consolidation of holdings is of great importance. In comparison with the so-called Vereinödung (consolidation of holdings together with re-location of farmsteads on to their consolidated land) of the 18 th century in Upper Swabia, to which subject the author has devoted a previous paper, it is characteristic for Switzerland that more initiative was shown by the state and that re-arrangement of farms was carried out with greater intensity and affected even early settled areas of villages. The re-location of dispersed farmsteads on to their now consolidated land is however less frequent in Switzerland than in the area of hamlet settlements of eastern Upper Swabia. These points show clearly that during the last 200 years the entire area around Lake Constance has undergone a thorough change in landscape as regards settlement and field patterns.